Processamento de imagens digitais e análise espacial para o estudo da susceptibilidade a incêndios florestais nas regiões do Apiaú e Ribeiro Campos - RR - Silva, Gladis de Fátima Nunes da (2006)
This study has forest analyzes the environment factors which contribute to the occurrence of the environment fires in Apiaú and Ribeiro Campos localities in Mucajaí - RR with the employment of image processing techniques and space analyses through the Analytical Hierarchy Process (AHP).